1993
DOI: 10.1111/j.1365-2559.1993.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary low‐grade B‐cell lymphoma of the conjunctiva: a mucosa‐associated lymphoid tissue type lymphoma

Abstract: We describe the clinical presentation, morphology, immunophenotypic features and molecular biology of seven cases of conjunctival lymphoid infiltration. In five cases there was either immunophenotypic or molecular evidence of B-cell lymphoma. Each of these cases showed the morphological, immunophenotypic and molecular feature of low-grade B-cell lymphoma of mucosa-associated lymphoid tissue (MALT) type. The findings suggest that most conjunctival lymphomas are of this type and explains their uniformly favourab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 33 publications
2
32
1
3
Order By: Relevance
“…MALT lymphoma has been reported to occur in the ocular adnexa (13,14). In the present study, MALT lymphoma constituted 86% of the classifiable primary ocular adnexal lymphomas.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…MALT lymphoma has been reported to occur in the ocular adnexa (13,14). In the present study, MALT lymphoma constituted 86% of the classifiable primary ocular adnexal lymphomas.…”
Section: Discussionsupporting
confidence: 51%
“…Some authors have used PCR analysis to detect IgH clonality of ocular adnexal lymphoid lesions (5,6,14,(17)(18)(19)(20), but it is not clear how often PCR reveals the clonality of ocular adnexal MALT lymphomas. We detected a monoclonal B-cell growth in 55% of the cases of MALT lymphoma by using PCR; in general, the PCR technique demonstrates the presence of a monoclonal B-cell population in 25 to 70% of the cases of MALT lymphoma (21).…”
Section: Discussionmentioning
confidence: 99%
“…Historically diagnosed as small lymphocytic lymphoma of the ocular adnexa, this low-grade B-cell lymphoma is frequently of MALT origin [126]. The clinical course is indolent and the risk for dissemination is low.…”
Section: Ocular Adnexa and Lacrimal Glandmentioning
confidence: 99%
“…In 1990 Bron et al [1] reported a patient presenting with an indolent tumor of the bulbar conjunctiva and raised the question of a possible MALT origin. Wotherspoon et al [14] examined biopsies of patients with conjunctival lymphoid infiltrates using histological, immunohistochemical and molecular genetic techniques. They found features of low-grade Bcell lymphoma of the MALT, suggesting that most conjunctival lymphomas are of this type.…”
Section: Discussionmentioning
confidence: 99%